2019
DOI: 10.1186/s12887-019-1581-9
|View full text |Cite|
|
Sign up to set email alerts
|

Factors influencing childhood anaemia in Bangladesh: a two level logistic regression analysis

Abstract: Background Anemia is not only a major public health problem among children in developing countries, it is also an important predictor for their future growth and development. The objective of this study was to identify possible factors associated with anemia among pre-school children in Bangladesh after removing a cluster effect of the population, and to determine the prevalence of this condition. Methods Data for this study was extracted from the 2011 Bangladesh Demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
7
11
0
1
Order By: Relevance
“…We found that health status of the mother which include maternal anemia and BMI was highly associated with childhood anemia in Bangladesh, which is in line with prior studies [ 23 25 , 40 ]. Maternal anemia works in several pathways.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that health status of the mother which include maternal anemia and BMI was highly associated with childhood anemia in Bangladesh, which is in line with prior studies [ 23 25 , 40 ]. Maternal anemia works in several pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Shakur et al found that birth weight and month of birth have a significant association with children’s hemoglobin status [ 17 ]. Several studies have identified the determinants of childhood anemia based on nationally representative data from the Bangladesh Demography and Health Survey’2011 [ 23 26 ]. However, none of the studies have considered the impact of household food security on childhood anemia.…”
Section: Introductionmentioning
confidence: 99%
“…Random intercept models were used to allow the intercept of the regression model to vary across communities/towns, which could account for intra-correlated nested data. Two-level logistic regression models are commonly used in studies using similar sampling method as ours [49,50]. Univariate logistic models were first used to examine the significance of the association between each covariate and outcome variable.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We demonstrate a prevalence (3·9%, 37/941) of severe anaemia in children with SCA, aged between five and 12 years old, living in northern Nigeria, a low resource setting. Severe anaemia was associated with risk factors of poverty 15 , including the lower educational level of the head of household, and a greater number of people, particularly children, living per room in the household. The risk factors identified reflect the low socioeconomic status and educational gaps prevalent in northern Nigeria and other regions in sub‐Saharan Africa, where more than a third of the global burden of SCD is found 16 …”
Section: Discussionmentioning
confidence: 99%